Implied volatility and contagion in the options market - Prima Sakti, Muhammad Rizky; Mohamad, Azhar (2014)

(untitled)
Among options traders, implied volatility is regarded as one of the most important variables for determining profitability in options trading. Implied volatility implies the future underlying stock volatility, and whilst it cannot predict market direction, it can forecast the stock’s potential for large fluctuations in the future. Once the implied volatility has been calculated, the traders can estimate how high or low the stock might swing by the option’s expiration and this estimation helps traders to make informed trading decisions. In this paper, we examine the information content of the implied volatility of call options in the Malaysian stock market. We use a daily dataset for 100 trading days for a period between November 2013 and February 2014. Our findings suggest that, for the Malaysian market, although implied volatility does contain some relevant information about future volatility, it is a less accurate predictor than historical volatility.